1997
DOI: 10.1124/mol.51.5.809
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Modes of Action of Methylglutamate Derivatives on the Excitatory Amino Acid Transporters, EAAT1 and EAAT2

Abstract: SUMMARYWe have investigated the mechanism of action of a series of glutamate derivatives on the cloned excitatory amino acid transporters 1 and 2 (EAAT1 and EAAT2), expressed in Xenopus laevis oocytes. The compounds were tested as substrates and competitive blockers of the glutamate transporters. A number of compounds showed contrasting mechanisms of action on EAAT1 compared with EAAT2. In particular, (2S,4R)-4-methylglutamate and 4-methylene-glutamate were transported by EAAT1, with K m values of 54 M and 391… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
97
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 27 publications
8
97
0
Order By: Relevance
“…Hydropathy analysis revealed that these transporters would possess six membrane spanning helices in the NH 2 -terminal part and long hydrophobic stretches in the COOH-terminal half of the molecules (data not shown) as has been demonstrated for EAATs cloned to date [1,5,10,15,19]. These observations support recent findings that the COOH-terminal large hydrophobic regions of these subtypes, in common, consist of structural elements [7] that appear to be critical for coupling of the fluxes of Na + , K + and glutamate [11,23,26], although the precise membrane topology of this region remains controversial.…”
Section: Discussionsupporting
confidence: 79%
“…Hydropathy analysis revealed that these transporters would possess six membrane spanning helices in the NH 2 -terminal part and long hydrophobic stretches in the COOH-terminal half of the molecules (data not shown) as has been demonstrated for EAATs cloned to date [1,5,10,15,19]. These observations support recent findings that the COOH-terminal large hydrophobic regions of these subtypes, in common, consist of structural elements [7] that appear to be critical for coupling of the fluxes of Na + , K + and glutamate [11,23,26], although the precise membrane topology of this region remains controversial.…”
Section: Discussionsupporting
confidence: 79%
“…SYM-induced excitotoxicity in CGC was completely blocked by an NMDA receptor antagonist, MK-801, reminiscent with the finding that glutamate or domoic acid-induced Ca 2 þ influx and toxicity in CGC is preferentially blocked by NMDA receptor blockers. 21,22 Our results suggest that SYM-induced apoptosis is due to the accumulation of glutamate resulting from inhibition of EAATs 14 or enhanced glutamate release due to the activation of kainate receptors, 15,22 thus in turn Figure 5 VPA delays the accumulation of GAPDH in the nuclei of CGC following SYM treatment. (A) Immunohistochemistry of GAPDH.…”
Section: Discussionmentioning
confidence: 71%
“…However, the lack of kainite-induced death of CGC speaks against the latter possibility. 23 The role of EAATs in SYM-induced apoptosis is further supported by the observations that EAAT inhibitors exacerbate endogenous glutamate-induced excitotoxicity through NMDA receptor activation, 24 and that SYM is one of the most potent inhibitors of EAATs, 14 which are expressed in CGC neurons. 25,26 Our pioneering studies show that GAPDH overexpression and nuclear translocation is involved in apoptosis of several cell types subjected to various insults.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Oocytes were harvested from X. laevis as described previously (16), and 50 nl of cRNA was injected into defoliculated stage V oocytes and incubated in standard frog Ringer's solution called ND96 (96 mM NaCl, 2 mM KCl, 1 mM MgCl 2 , 1.8 mM CaCl 2 , 5 mM HEPES, pH 7.55) supplemented with 2.5 mM sodium pyruvate, 0.5 mM theophylline, 50 g/ml gentamicin. Current recordings were made 2-5 days later using the two-electrode voltage clamp technique with a Geneclamp 500 amplifier (Axon instruments, Foster City, CA) interfaced with a MacLab 2e chart recorder (ADI Instruments, Sydney, Australia) using the Chart software and a Digidata 1200 (Axon Instruments), which is controlled by an IBM-compatible computer installed with pClamp software, version 7.0 (Axon Instruments).…”
Section: Methodsmentioning
confidence: 99%